2010
DOI: 10.1161/atvbaha.110.211581
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Synthase Expression and Functional Response to Nitric Oxide Are Both Important Modulators of Circulating Angiogenic Cell Response to Angiogenic Stimuli

Abstract: Objective-Circulating angiogenic cells (CACs), also termed endothelial progenitor cells, play an integral role in vascular repair and are functionally impaired in coronary artery disease (CAD). The role of nitric oxide (NO) in CAC function is poorly understood. We hypothesized that CAC migration toward angiogenic signals is modulated by both NO synthase (NOS) expression and functional response to NO. Methods and Results-Similar to endothelial cells, CAC chemotaxis to vascular endothelial growth factor (VEGF) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 41 publications
4
54
0
Order By: Relevance
“…Interestingly, eNOS appears to be an important modulator of CAC function similar to ECs (40) and mobilization from the bone marrow (2). We have shown that eNOS activity is required for CAC chemotaxis (40).…”
Section: Regenerative Capacity Of the Endothelium And Cacsmentioning
confidence: 81%
See 3 more Smart Citations
“…Interestingly, eNOS appears to be an important modulator of CAC function similar to ECs (40) and mobilization from the bone marrow (2). We have shown that eNOS activity is required for CAC chemotaxis (40).…”
Section: Regenerative Capacity Of the Endothelium And Cacsmentioning
confidence: 81%
“…We have shown that eNOS activity is required for CAC chemotaxis (40). Furthermore, in CAD patients, impairment of NOS expression and NO bioavailability, rather than response to NO, may contribute to dysfunction of CACs and limit their regenerative capacity.…”
Section: Regenerative Capacity Of the Endothelium And Cacsmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition to endothelial cells, eNOS is present on circulating blood cells, including circulating angiogenic MNCs, and on circulating microparticles, therefore its regulation impacts on the overall homeostasis of the vascular tree controlling blood flow restoration via angiogenesis, vasculogenesis, and arteriogenesis (23)(24)(25)(26). Together with neuronal NOS (nNOS), eNOS is constitutively expressed.…”
Section: The Enos Signaling Pathway and The Control Of Angiogenesismentioning
confidence: 99%